2012
DOI: 10.3390/ijerph9082728
|View full text |Cite|
|
Sign up to set email alerts
|

Lifestyle and Health among Spanish University Students: Differences by Gender and Academic Discipline

Abstract: Today the need to analyze health behaviour from a gender perspective is as imminent as ever, particularly at university, where the number of women who register is on the rise and has exceeded the number of male students worldwide. We carried out a prevalence study aimed at analyzing Spanish university students’ lifestyles and identify differences according to gender and academic discipline. Of 3,646 eligible subjects doing university courses related to health (Group A), education (Group B) and other profession… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
81
7
29

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(128 citation statements)
references
References 39 publications
(43 reference statements)
8
81
7
29
Order By: Relevance
“…Estes resultados, aliado a achados semelhantes de estudos internacionais, 4,5,16,20 sugerem a importância de intervenções que possibilitem e motivem a prática de atividade física entre estudantes universitários, bem como a importância da criação de programas de orientação nutricional e implantação de restaurantes universitários nos campi universitários visando uma alimentação mais saudável e balanceada entre os estudantes.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Estes resultados, aliado a achados semelhantes de estudos internacionais, 4,5,16,20 sugerem a importância de intervenções que possibilitem e motivem a prática de atividade física entre estudantes universitários, bem como a importância da criação de programas de orientação nutricional e implantação de restaurantes universitários nos campi universitários visando uma alimentação mais saudável e balanceada entre os estudantes.…”
Section: Discussionunclassified
“…1 O EV pode ser influenciado por diversos comportamentos, tais como, prática de atividades físicas, hábitos alimentares, uso de tabaco, relacionamento com a família e amigos, consumo de bebidas alcoólicas, sexo seguro, controle do estresse e visão da vida. [2][3][4][5] Cada vez mais crescem as evidências de que o modo de viver representa o fator diferencial para a saúde e a qualidade de vida no mundo contemporâneo, independente da idade ou condição social. 6 Considerando a influência do estilo de vida na saúde das pessoas, este assunto tem se constituído uma constante preocupação, uma vez que baixos níveis de saúde e bem-estar podem provocar consequências negativas, especialmente entre jovens universitários, que constituem um grupo vulnerá-vel, pois com a entrada no ensino superior ocorrem questionamentos de valores, crenças e atitudes empregados pela família no processo de educação.…”
Section: Introductionunclassified
“…(5,15) A research with Spanish college students showed that women were less active and had a more sedentary lifestyle than men and therefore the realization of specific intervention actions for women was recommended. (3) Data pointing out that college students who live with their families had better nutritional habits have also been found, and that those enrolled in the first year of college tend to present improved health behaviors when compared with students in subsequent periods. (15) As for the overweight, this study observed a higher percentage of cases in comparison with the findings among American university students.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies aimed at comprehending, controlling and monitoring such behaviors point out their high prevalence reflected on sedentary habits, eating disorders, traffic accidents, consumption of tobacco, alcohol and other drugs, and violence against oneself and others. (1)(2)(3)(4)(5) Wang et al observed a high percentage of university students who presented unhealthy lifestyles. The researchers stood up to defend the need for taking social and territorial contexts into account in the preparation of plans toward minimizing the morbidity-mortality loads caused by non-transmissible chronic diseases, as well as the need for improving the quality of life of this population by means of regional development programs of healthcare education that may mitigate social-spatial inequalities.…”
Section: Introductionmentioning
confidence: 99%
“…O estilo de vida é objeto de estudo de pesquisadores da área da saúde, por ser um dos mais importantes determinantes da saúde da população 1,2 . Entretanto, apesar de toda informação a respeito do tema, pesquisas comportamentais revelam que entre estudantes universitários parece ocorrer aumento dos índices e da quantidade de hábitos considerados de risco para desenvolvimento de doenças crônico-degenerativas 3,4 .…”
Section: Introductionunclassified